Adiponectin negatively correlates with alcoholic and non‐alcoholic liver dysfunction: Health check‐up study of Japanese men. Issue 3 (26th July 2012) - Hamano, Mina; Kamada, Yoshihiro; Kiso, Shinichi; Furuta, Kunimaro; Kizu, Takashi; Chatani, Norihiro; Egawa, Mayumi; Takemura, Takayo; Ezaki, Hisao; Yoshida, Yuichi; Watabe, Kenji; Hamasaki, Toshimitsu; et al.
<x xml:space="preserve">Abstract</x> Aim: Central obesity, insulin resistance and alcohol consumption are thought to be major risk factors for fatty liver formation. Adiponectin (APN) prevents fatty liver formation, and its serum levels are lower in subjects with central obesity and/or insulin resistance. The aim of this study was to explore the association among serum APN levels, central obesity, insulin resistance and liver dysfunction with or without fatty liver classified by alcohol consumption in healthy subjects. Methods: A total of 5588 Japanese male subjects who underwent a health check‐up were classified into three groups according to alcohol consumption: non‐ or light drinkers (15 g/day ≥ ethanol); mild drinkers (15 g/day < ethanol ≤ 30 g/day); and moderate‐ or heavy drinkers (30 g/day < ethanol). Central obesity and insulin resistance were assessed by waist circumference (WC) and Homeostasis Model of Assessment – Insulin Resistance (HOMA‐IR), respectively. Results: WC was significantly increased, while HOMA‐IR was significantly decreased according to the extent of alcohol consumption. Serum alanine aminotransferase levels were significantly lower and serum APN levels were significantly higher in mild drinkers than in the other two groups. Multiple linear regression analysis showed that serum APN level served as the significant and independent determinant for liver dysfunction in the subjects with fatty liver, irrespective of alcohol consumption. However, WC became a non‐significant determinant of liver dysfunction as alcohol consumption increased. Conclusion: Hypoadiponectinemia is a significant determinant for steatotic dysfunction for all levels of alcohol consumption, but central obesity was not a significant determinant for alcoholic fatty liver‐induced liver dysfunction.